Psychosocial Rehabilitation: Some Lessons Learned From Natural Disaster in Iran - Fardin Alipour (Health in Emergencies & Disasters Quarterly, 2016)
Background: Disasters have adverse impacts on different aspects of human life. Psychosocial Rehabilitation is one of the fields which is usually overshadowed and ignored by physical rehabilitation or its importance does not receive proper attention. This research attempts to study some lessons learned from Psychosocial Rehabilitation based on disaster experiences in Iran. Materials and Methods: This study has a conventional qualitative content analysis design. The participants of study were 15 people with direct experience of earthquake and 12 experts in this field. The study sample was selected by purposeful sampling method and the data were collected by semi-structured interviews. Results: Lack of a suitable system to deliver Psychosocial Rehabilitation, challenge in establishing balance between short-term and long-term social and mental needs, lack of mental and social experts, inefficiency in using social capital and capacities are the most important lessons learned in this field. Conclusion: Lack of awareness of mental and social problems of affected people after disaster is one of the most important barriers in successful and stable rehabilitation. Psychosocial Rehabilitation requires a suitable structure and planning for all stages of disaster management.